Свиданий не будет: [роман] / Фридрих Незнанский - Незнанский Фридрих Евсеевич (Господин адвокат, 1998)
Экземпляры: аб. (2009) / Инвентарный номер: 52850 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44